Sequence alignment files of the V4 hypervariable region of the 16S rRNA used for the phylogenetic analysis - Galan, Maxime; Razzauti, Maria; Bard, Emilie; Bernard, Maria; Brouat, Carine; Charbonnel, Nathalie; Dehne-Garcia, Alexandre; Loiseau, Anne; Tatard, Caroline; Tamisier, Lucie; Vayssier-Taussat, Muriel; Vignes, Hélène; et al. (Dryad Digital Repository, 2016)
This ZIP file contains the FASTA files of the most abundant sequences from the 12 pathogenic OTUs (Bartonella, Borrelia, Ehrlichia, Orientia, Rickettsia, Streptobacillus and Mycoplasma_OTU_1 to Mycoplasma_OTU_6) and reference sequences from Silva ribosomal database v119 for the same genera.